Les Plaies Penetrantes Par Armes Blanches Et A Feu A N’djamena, Tchad: Une Epidemie Silencieuse ? - O, Choua; K, Rimtebaye; M, Adam Adami; G, Bekoutou; M A., Anour (European Scientific Journal, ESJ, 2016)
Aim: the aim of this study was to report the experience of the General Hospital of National Reference in N'djamena (Chad) in the management of penetrating wounds. Patients and methods: This was a prospective study ranging from 01/07/2013 to 30/06/2014. Were included all patients undergoing penetrating stab or firearm wound. The studied variables were: age, sex, and type of trauma, prehospital delay, transport, and the treatment. The length of hospital stay, morbidity and mortality were also studied. Results: the series included 129 patients: 120 men (93%) and 9 women (7%). penetrating trauma constituted 22.7% of the 569 surgical emergency admissions. They were caused by a knife and a gun in respectively 112 (77.5%) and 17 (13.2%) patients. Brawls and assaults were the cause of trauma in 78 cases, respectively (60.5%) and 47 cases (36.4%). The cause was accidental in 4 cases (3.1%). The most used wounding agent was the knife in 100 cases (77.5%), followed by firearms in 17 cases (13.2%) and other sharp objects in 12 cases (9.3%). The admission average time was 3,7h. Patients arrived mostly by public transport. Penetrating wounds were respectively 67 cases in thoracic, 50 cases in abdominal and in 2 intracerebral cases. Treating chest wounds included: in 50.7% of cases right thoracic drain, 46.3% of left thoracic drain and 3% of bilateral thoracic drain. For abdominal penetrating wounds laparotomy was the rule. Surgical treatment in these cases: 6 gastric sutures, 25 sutures and 4 resection of the small intestine, and 10 sutures, plus 2 resections of the colon, 3 negative laparotomies. Similarly, the diaphragm, the liver, and spleen injuries had proper treatment. Elsewhere, two intra brain knives were extracted. The average stay was 8.9 days. Morbidity was 6.2% and mortality 3.1%. Conclusion: penetrating trauma is a real public health problem in N'Djamena related to brawls and aggressions. Knife is the most used agent.